ESTIMATION OF SUBGRADE STRENGTHENING INFLUENCE USING SOILCEMENT ELEMENTS - Petrenko, V. D.; Tiutkin, O. L.; Sviatko, I. O. (Science and Transport Progress, 2016)
Purpose. The aim of this work is to identify dependencies and options to strengthen the roadbed and a weak base by grouting piles. Analysis of software package SCAD to assess the effect of the selected option of strengthening the construction of spatial subgrade models. Methodology. In this paper the method of calculation of the soil mass in the software package SCAD is considered, which is a universal accounting system of finite-element analysis of structures and is focused on solving problems of designing buildings and structures rather complex structure. The finite element method is among the most modern and effective methods for the calculation of structures for various purposes. In the simulation, we get a complete picture of the stress-strain state of the study area, as well as the value of the limit load, rainfall, and so on. The spatial model based on the finite element volume, to better address the real characteristics of the soil mass, meets all the geometric characteristics of size and natural subgrade and the top structure the path that has been adopted in Ukraine. Findings. It was found that the most effective option to strengthen the roadbed, when applying grouting piles at the base of the subgrade and body, is to strengthen the five piles. At the same time there is even strengthen the soil mass at the level of 25 … 30% of the entire depth. However, even with the strengthening of the only two piles at the base of the effect of the strengthening of 14.1%. Established equation is linear and describes the decrease in strain. Taking into account the results of the research can be concluded that the consolidation is proportional to the depth with any number of piles. The dependence of the strain on the number of piles adheres to a polynomial function. Strengthening the bases of the subgrade and body depth also occurs in proportion with any number of piles. Originality. Design scheme generation algorithm for the calculation of the subgrade on a weak basis by finite element method was determined. The selection of strength characteristics of soils and the design parameters for use during the numerical simulation was completed. Load process simulation of the system by rolling stock was grounded. Practical value. Analysis of stress-strain state of «weak base-subgrade» allows you to see the basic laws work the soil and take the necessary measures to enhance the cross-section profile of jet-grouting elements.